Time course of indirect reply comprehension in the young and older adults: an event-related potential study - Feng, Wangshu; Zhang, Xiaokun; Wang, Weijuan; Fan, Lin (Frontiers in Psychology, 2025)
IntroductionIn verbal communication, speakers often use implicit utterances that need listeners to interpret via pragmatic inference. As individuals age, their ability to make efficient and accurate pragmatic inferences may decline, leading to communication difficulties.ObjectivesThis study examined the cognitive aging phenomenon of pragmatic inference and its neural mechanisms using EEG recordings.MethodsParticipants were presented with dialogues involving direct and indirect replies and were required to judge the speaker's intended meaning based on the context.ResultsYounger participants outperformed older participants in task accuracy for indirect replies. Both groups exhibited an increased N400 for indirect replies in the late stages of reply presentation. However, younger participants exhibited greater N400 effects in the early and middle stages, something notably absent in older participants.ConclusionThese findings suggest that older adults have a reduced ability to make pragmatic inferences, likely due to difficulties in dynamically enriching semantic content in real-time speech.